Ginsenoside Rk1 reprograms ‘cold’ cancer cell membranes into a ‘hot’ antigen repertoire for highly immunogenic cancer vaccines - Fangming Dong; Linlin Qu; Lebin Wang; Jing Zhao; Zhiguang Duan; Xueqing Yu; Xiaoxuan Ma; Daidi Fan (Chemical Engineering Journal, 2026)

Adaptive rotary tillage depth control with RBF-ADRC based on time-series prediction of tractor chassis pitch angle - Xuekai Huang; Xiaochan Wang; Yinyan Shi; Jing Yuan; Yanxin Wang; Lebin Lin; Jiajun Xu; Yongnian Zhang (Computers and Electronics in Agriculture, 2026)

Adaptive fuzzy coordinated control of orchard mowing robots using cutter torque-feedforward–SMC and chassis ICOA–Smith–RBF–PID strategies - Xuekai Huang; Zheng Wang; Xiaochan Wang; Yinyan Shi; Xiaopeng Huang; Bowei Wang; Lebin Lin; Yanxin Wang (Computers and Electronics in Agriculture, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Corrigendum to “Porphyrinized carbon quantum dots: A novel antibacterial nanomaterial for visualized and broad-spectrum treatment of drug-resistant infected wounds” [Chem. Eng. J. Volume 522, 15 October 2025, 166981] - Mengwei Zhang; Jingjing Ye; Jingyao Zhang; Zijian Tian; Lebin Gan; Qiang Wang; Rui Li; Diya Sun; Zishuo Pei; Ming Li; Minghui Liang; Tianbing Wang (Chemical Engineering Journal, 2025)

Porphyrinized carbon quantum dots: A novel antibacterial nanomaterial for visualized and broad-spectrum treatment of drug-resistant infected wounds - Mengwei Zhang; Jingjing Ye; Jingyao Zhang; Zijian Tian; Lebin Gan; Qiang Wang; Rui Li; Diya Sun; Zishuo Pei; Ming Li; Minghui Liang; Tianbing Wang (Chemical Engineering Journal, 2025)

The effect of USP17 knockdown on autophagic ferroptosis in gastric cancer by regulating the BNIP3–NCOA4–FTH1 axis - Jintao Tang; Lebin Yang; Xiongying Chen; Kai Yin; Chunyun Wang (Journal of Molecular Histology, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Recommended risk screening values for Cd in high geological background area of Guangxi, China - Naichuan Xiao; Fopeng Wang; Lebin Tang; Liangliang Zhu; Bo Song; Tongbin Chen (Environmental Monitoring and Assessment, 2022)

Return Encounters in Emergency Department Patients Treated with Phenobarbital Versus Benzodiazepines for Alcohol Withdrawal - Jacob A. Lebin; Anita Mudan; Charles E. Murphy; Ralph C. Wang; Craig G. Smollin (Journal of Medical Toxicology, 2022)
Introduction Phenobarbital has been successfully used in the emergency department (ED) to manage symptoms of alcohol withdrawal, but few studies have reported outcomes for ED patients who receive phenobarbital and are discharged. We compared return encounter rates in discharged ED patients with alcohol withdrawal who were treated with benzodiazepines and phenobarbital. Methods This is a retrospective cohort study conducted at a single academic medical center utilizing chart review of discharged ED patients with alcohol withdrawal from July 1, 2016, to June 30, 2019. Patients were stratified according to ED management with benzodiazepines, phenobarbital, or a combination of both agents. The primary outcome was return ED encounter within three days of the index ED encounter. Multivariate logistic regression identified significant covariates of an ED return encounter. Results Of 470 patients who were discharged with the diagnosis of alcohol withdrawal, 235 were treated with benzodiazepines, 133 with phenobarbital, and 102 with a combination of both. Baseline characteristics were similar among the groups. However, patients who received phenobarbital were provided significantly more lorazepam equivalents compared to patients who received benzodiazepines alone. Treatment with phenobarbital, alone or in combination with benzodiazepines, was associated with significantly lower odds of a return ED visit within three days compared with benzodiazepines alone [AOR 0.45 (95% CI 0.23, 0.88) p = 0.02 and AOR 0.33 (95% CI 0.15, 0.74) p = 0.007]. Conclusions Patients who received phenobarbital for alcohol withdrawal were less likely to return to the ED within three days of the index encounter. Despite similar baseline characteristics, patients who received phenobarbital, with or without benzodiazepines, were provided greater lorazepam equivalents the ED.

Emergent chikungunya fever and vertical transmission in Yunnan Province, China, 2019 - XiaoXiong Yin; Ting-Song Hu; HaiLin Zhang; YongHua Liu; ZhiJian Zhou; LeBin Liu; Ping Li; YiYin Wang; ZhaoLan Yang; Jing Yu; SiYu Chen; Fu-Qiang Zhang (Archives of Virology, 2021)

Novel TBX22 mutations in Chinese nonsyndromic cleft lip/palate families - Jiewen Dai; Chen Xu; Guomin Wang; Yun Liang; Teng Wan; Yong Zhang; Xiaofeng Xu; Lebin Yu; Zonggang Che; Qiqing Han; Dandan Wu; Yusheng Yang (Journal of Genetics, 2018)

Transgenic Bt cotton driven by the green tissue-specific promoter shows strong toxicity to lepidopteran pests and lower Bt toxin accumulation in seeds - Qing Wang; Yi Zhu; Lin Sun; Lebin Li; Shuangxia Jin; Xianlong Zhang (Science China Life Sciences, 2016)